Physical activity and sedentary time in a multimodal lifestyle intervention in prodromal Alzheimer's disease: The MIND‐ADMINI pilot trial. (31st December 2021) - Thunborg, Charlotta; Rosenberg, Anna; Barbera, Mariagnese; Coley, Nicola; Ekblom, Maria; Ekblom, Örjan; Levak, Nicholas; Solomon, Alina; Kivipelto, Miia
Abstract: Background: Alzheimer's disease (AD) is multifactorial. Interventions simultaneously targeting multiple risk factors are most likely to be effective, as demonstrated in the 2‐year Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER). While patients with prodromal AD represent a group with high risk of progressing to dementia, no trials have tested the feasibility of multimodal interventions in prodromal AD. The main purpose of the MIND‐ADMINI was to evaluate the overall adherence to such multimodal intervention. This sub‐study focuses on exploratory outcomes which included physical performance and physical activity (PA) levels. Method: MIND‐ADMINI is a 6‐month multicenter (Sweden, Finland, Germany, France) randomized controlled pilot trial. Participants with prodromal AD, between 60 and 85 years were randomized into three groups: usual care (control (C)), multidomain lifestyle intervention combining nutritional guidance, cognitive training, exercise, and careful monitoring of vascular risk factors (ML), or multidomain lifestyle intervention+medical food (ML+MF) (Fortasyn Connect). The multidomain lifestyle intervention was based on the FINGER model and included a progressive aerobic‐ and strength training program. Moderate to vigorous physical activity (MVPA), light activity, step counts, and time (min/day) spent sedentary were evaluated using data from a hip‐worn accelerometer. For each outcome, 6‐month values were regressed on baseline to estimate change. Results: Baseline accelerometry data was available for 66 of 69 participants in Sweden, Finland, and France. At the 6‐month follow‐up, accelerometry data from 55 participants was included. At baseline mean age (SD) was 72, 9 (6, 2) years, 50, 7% were men, and MMSE score was 27, 6 (1, 6) points. No significant values were found. At follow‐up, all groups increased their sedentary time, C (8, 3%), ML (9, 3%) and ML+MF (1, 6%). Increased step count (3, 4%) time in MVPA (2, 8%) and light activity (9, 5%) was observed during follow‐up in the ML+MF group. Conclusions: Measurement of physical activity level using a hip‐worn accelerometer was feasible in this population. The observed increased time in MVPA, light activity and step counts in ML+MF group at the same time as sedentary time increased in all three groups between baseline and 6‐months follow‐up highlight the importance of physical activity as a part of multidomain lifestyle interventions in persons with prodromal AD.